JENIS-JENIS MEDIA YANG DIGUNAKAN OLEH GURU PADA MATERI EVOLUSI DI KELAS XII SMA DI KOTA PONTIANAK - Salsabila, Alfiya; Candramila, Wolly; Mardiyyaningsih, Asriah Nurdini (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Instructional media refers to various tools or materials used in the learning process to support delivering information, concepts, or subject matter to students more effectively and engagingly. Instructional media plays a crucial role in education, especially when teaching the concept of evolution. Therefore, it is necessary to explore the use of instructional media in schools. This study describes the types of instructional media and how teachers utilize them to deliver the concept of evolution to twelfth-grade high school students in Pontianak City. The findings of this research are expected to provide recommendations for the most effective instructional media to enhance students' understanding of evolutionary concepts. This study employed a qualitative survey method. Participant sampling was carried out using a participatory technique, where data collection was conducted only in schools that granted permission for the research. Data were collected through a questionnaire containing statements regarding teaching challenges, explanations of lesson plan (RPP) development (including content coverage, learning objectives, approaches, models, and methods), as well as the selection and use of instructional media for teaching evolution in twelfth-grade high school classes. The results of the study revealed that a total of nine types of single and combined instructional media were used by teachers in 19 high schools across Pontianak City to teach the topic of evolution.